GUIDELINES FOR ORGANIZATION MANAGEMENT SYSTEM HORIZONTALITY LEVEL ASSESSMENT - A. Dolgaya (Publishing House of the State University of Management, 2016)
There in the article the guideline for management system assessment is proposed on the basis of organizational horizontality concept developed by the author. The horizontal management system is defined as a complex of directed interconnection of adhoc culture and process based structure implemented in the client oriented management model. In this paradigm the horizontality indicator is shaped as an integrated index evaluating by Liebig’s law the minimum of parameters: client orientation, process structuring, adhocracy compliance of culture.